Epidemiology of podoconiosis in Ethiopia: a systematic review and meta-analysis protocol - Alemnew, Birhan (BMJ Open, 2020)
INTRODUCTION: Podoconiosis is a non-filarial swelling of the lower extremity endemic in tropical regions, North America and India. The aetiology and pathophysiology of the disease remain unknown. We propose conducting a systematic review and meta-analysis to evaluate the burden and risk factors of podoconiosis in Ethiopia reported in studies from 2009 to 2019. METHODS AND ANALYSIS: We will search the following electronic databases: PubMed (MEDLINE), EMBASE, Hinari, Cumulative Index to Nursing and Allied Health Literature, ISI (Web of Science) and Google Scholar. Medical subject headings will be used to extensively search relevant literature on electronic databases using related keywords such as epidemiology or prevalence, magnitude or burden, podoconiosis, and Ethiopia. Grey literature and manual search will also be performed to retrieve unindexed research articles. Two reviewers will screen all retrieved articles, conduct data extraction and then critically appraise all identified studies. We will analyse data using STATA V.14 statistical software. We will demonstrate pooled estimates of podoconiosis and associated factors with effect size and 95% CI. The presence of heterogeneity among studies will be examined by forest plot as well as the I(2) heterogeneity test. Potential causes of heterogeneity will be explored by carrying out sensitivity and subgroup analyses. The presence of publication bias will also be examined by observing funnel plots and objectively by Egger’s regression test. If the funnel plot is asymmetric and/or Egger’s test was found to be statistically significant (p<0.05), the trim and fill (Duval and Tweedie’s) analysis will be performed. ETHICS AND DISSEMINATION: The study will use publicly available data and will not identify the authors of the publication by name. In light of these and as has been indicated, research ethics clearance is not required for evidence syntheses in such reviews. The results of this study will be published in a peer-reviewed journal and presented at national and international conferences. PROSPERO REGISTRATION NUMBER: CRD42019127459.